A time‐to‐event analysis on air pollutants with the risk of cardiovascular disease and mortality: A systematic review and meta‐analysis of 84 cohort studies. Issue 2 (13th March 2020) - Pranata, Raymond; Vania, Rachel; Tondas, Alexander Edo; Setianto, Budhi; Santoso, Anwar
Abstract: Objective: Air pollution is one of the most substantial problems globally. Aerodynamic toxic of particulate matter with <10 mm in diameter (PM10 ), or <2.5 mm (PM2.5 ), as well as nitric dioxide (NO2 ), have been linked with health issues. We aimed to perform a comprehensive analysis of the time‐to‐event for different types of air pollutants on cardiovascular disease (CVD) events based on cohort studies. Methods: A comprehensive search on topics that assesses air pollution and cardiovascular disease with keywords up until July 2019 was performed. Results: There were a total of 28 215 394 subjects from 84 cohorts. Increased PM2.5 was associated with composite CVD [HR 1.10 (1.02, 1.19)], acute coronary events [HR 1.15 (1.12, 1.17)], stroke [HR 1.13 (1.06, 1.19)], and hypertension [HR 1.07 (1.01, 1.14)], all‐cause mortality [HR 1.07 (1.04, 1.09)], CVD mortality [HR 1.10 (1.07, 1.12)], and ischemic heart disease (IHD) mortality [HR 1.11 (1.07, 1.16)]. Association with AF became significant after removal of a study. Increased PM10 was associated with heart failure [HR 1.25 (1.04, 1.50)], all‐cause mortality [HR 1.16 (1.06, 1.27)], CVD mortality [HR 1.17 (1.04, 1.30)], and IHD mortality [HR 1.03 (1.01, 1.05)]. Increased of NO2 was associated with increased composite CVD [HR 1.15 (1.02, 1.29)], atrial fibrillation [HR 1.01 (1.01, 1.02)], acute coronary events [HR 1.08 (1.02, 1.13)], all‐cause mortality [HR 1.23 (1.14, 1.32)], CVD mortality [HR 1.17 (1.10, 1.25)], and IHD mortality [HR 1.05 (1.03, 1.08)]. Conclusion: Air pollutants are associated with an increased incidence of cardiovascular diseases, all‐cause mortality, and CVD mortality.